Three-Dimensional Confocal Microscopy : Volume Investigation of Biological Specimens - Stevens, John K.; Mills, Linda R.; Trogadis, Judy E. (Cell biology., 1994)
The integration of confocal microscopy and volume investigation has led to an unprecedented ability to examine spatial relationships between cellular structure and function. The goal of this book is to familiarize the reader with these new technologies and to demonstrate their applicability to a wide range of biological and clinical problems. Key Features* Volume investigation* Three-dimensional reconstruction* Fluroescent probe design* Biological applications of confocal microscopy, including calcium imaging, receptor movement, and diagnostic pathology* Confocal dat.